Tangential extremal principles for finite and infinite systems of sets II: applications to semi-infinite and multiobjective optimization - Mordukhovich, Boris S.; Phan, Hung M. (Mathematical programming, 2012)
This paper contains selected applications of the new tangential extremal principles and related results developed in Mordukhovich and Phan (Math Program 2011 ) to calculus rules for infinite intersections of sets and optimality conditions for problems of semi-infinite programming and multiobjective optimization with countable constraints.